PROFESIONALISME WARTAWAN DALAM PRESPEKTIF ISLAM - Nurma Anisah Trianis Tanti; Asep Gunawan; Noor Isna Alfaien (ADISAM PUBLISHER, 2025)
Journalist professionalism is important in the world of journalism, which includes principles such as honesty, accuracy, objectivity and social responsibility. This research aims to study the concept of journalist professionalism from an Islamic perspective, with a focus on how Islamic values can influence and influence the behavior of journalists as they carry out their work. Professionalism from an Islamic perspective must also be based on general ethical standards. This research uses the library research method or library study using the discourse analysis method. The research results show that Islam emphasizes the importance of integrity, justice and responsibility in the work of journalists. It is hoped that these principles will improve the quality of journalism and help build a fairer, more honest and responsible media. In addition, this research suggests that Muslim journalists always regulate Islamic values in their daily journalistic practices so that they can maintain the honor of their profession and produce greater benefits for society